Snap-Back Testing and Estimation of Parameters for Nonlinear Response of Shallow and Pile Foundations at Cohesive Soil Sites - Pender, M.J.; Algie, Thomas; Norazzlina, M.Sa‘don; Orense, R.P (2011)
We are working on the development of methods for analysing the earthquake response of foundations that make use of Soil-Foundation-Structure-Interaction (SFSI) as a means of incorporating nonlinear soil deformation effects and nonlinear geometrical effects into the earthquake resistant design of foundations. There are three challenges in this work. First, to incorporate adequately the nonlinear response of the soil during the earthquake. Second, to account for geometrical nonlinearity during the earthquake - that is loss of contact between various parts of the foundation and the underlying and/or adjacent soil. Examples of this are the gapping that develops between a pile shaft and the surrounding soil during cyclic lateral loading and the uplift beneath parts of a shallow foundation subject to rocking. Third, to obtain appropriate values for the soil parameters which describe the nonlinear response of the foundations. The main thrust of this paper is to show how snap-back testing is a most effective means of evaluating nonlinear soil behaviour. It will be demonstrated that snap-back testing is more convenient than using a shaking machine which applies sinusoidal excitation. The results will show how for the rocking of a shallow foundation and the cyclic lateral loading of a single pile, the damping and the stiffness can be estimated at increasing levels of lateral loading.